2013
DOI: 10.7899/jce-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Using computer-assisted learning to engage diverse learning styles in understanding business management principles

Abstract: Objective : Changes in small business and insurance present challenges for newly graduated chiropractors. Technology that reaches identified, diverse learning styles may assist the chiropractic student in business classes to meet course outcomes better. Thus, the purpose of our study is to determine if the use of technology-based instructional aids enhance students' mastery of course learning outcomes. Methods : Using convenience sampling, 86 students completed a survey assessing course learning outcomes, lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…To increase acceptance and understanding to all students, such content can take the form of traditional lectures and online delivery formats. Frost, Derby, and Haan [ 33 ] demonstrated that computer-assisted online content for business and management principles was a successful method to augment lecture-based content across multiple learning styles. Gleberzon [ 30 ] posited that chiropractic institutions lack a comprehensive model curriculum for business and management content.…”
Section: Discussionmentioning
confidence: 99%
“…To increase acceptance and understanding to all students, such content can take the form of traditional lectures and online delivery formats. Frost, Derby, and Haan [ 33 ] demonstrated that computer-assisted online content for business and management principles was a successful method to augment lecture-based content across multiple learning styles. Gleberzon [ 30 ] posited that chiropractic institutions lack a comprehensive model curriculum for business and management content.…”
Section: Discussionmentioning
confidence: 99%